Has South Africa been handed a poisoned chalice? Assessing the legal implications of the African Growth and Opportunity Act (AGOA) for South Africa's trade policy - Soyeju, Olufemi Olugbemiga (University of Pretoria, 2017)
AGOA is a US trade policy which defines and underpins the trade and investment relations between the US and sub-Saharan Africa. Essentially, AGOA extends duty free treatment to exports from eligible sub Saharan African countries. These preferences are aimed at promoting sub-Saharan African export earnings and stimulating their economic growth by giving them improved access to the US market. South Africa is one the few sub-Saharan African countries with a high utilization rate of the AGOA preferences, and has substantially benefited from AGOA. However, in order to ensure compliance with the eligibility requirements, an eligible sub-Saharan African country is subjected to constant, on-going surveillance and monitoring through the out of cycle review mechanism. Importantly, the US President has the prerogative to determine whether a sub- Saharan African country is eligible or remains eligible for the AGOA preferential treatment. The strict eligibility requirements and out of cycle review mechanism as well as the unilateral nature of AGOA deprive it of the necessary stability, certainty and predictability. Importantly, the out of cycle review mechanism has a chilling effect on trade policies of eligible sub-Saharan African countries. This is particularly true in respect of South Africa, whose trade policy is the primary subject of the study. Notwithstanding the economic benefits, the disadvantages and or risks associated with AGOA overwhelm same. The disadvantages and or risks are amply demonstrated by the recent development in which South Africa was compelled to remove Anti-Dumping duties and Sanitary and Phyto-Sanitary measures it had validly imposed on US poultry in return for retaining AGOA preferences. Consequently, it is contended that AGOA is not a non-reciprocal preferential scheme that it purports to be. Instead, it is de facto reciprocal or has reverse preferences embedded in it. This study therefore argues that South Africa is entitled to impose Anti-Dumping duties and the Sanitary and Phyo-Sanitary measures, provided that specific requirements are met and that the measures imposed by South Africa on US poultry are legal under the General Agreement on Tariffs and Trade (GATT) 1994 and the WTO law as long as the procedural and substantive requirements have been fulfilled. Consequently, the consistency thereof can only be tested using the WTO dispute settlement mechanism. Further, the study highlights the implications of removing the above-mentioned measures for South Africa's trade policy and explores various alternative trade arrangements which South Africa and other sub-Saharan African countries may pursue in order to ensure or secure a stable, transparent, reciprocal trade relation with the US.